Activation of peroxydisulfate by thermally‐treated natural siderite to degrade sulfamethazine: performance and mechanism. Issue 6 (8th April 2023) - Sun, Fuwei; Wang, Hao; Wang, Qiang; Chu, Ziyang; Liu, Haibo; Chen, Tianhu; Chen, Dong; Zou, Xuehua; Shu, Daobing; Wang, Hanlin
Abstract: Compared with synthetic materials, natural mineral materials have the advantages of low cost and easy availability. In the present study, magnetite was prepared by calcination of natural siderite under an N2 atmosphere and utilized as a heterogeneous material for sulfamethazine (SMT) degradation via peroxydisulfate (PDS) activation. Various characterizations demonstrated that the S600 (siderite calcinated at 600 °C for 1 h) had a high specific surface area (57.18 m 2 /g) and high electron transfer ability. Under 1 g/L S600 and 1 mM PDS, 99.9% and 50% of SMT (5 mg/L) and TOC were eliminated in 2 h, with a kinetic constant of 0.026 min −1 . Increasing the S600 dosage and PDS concentration favored SMT degradation, while inorganic anions and natural organic matter had the opposite effect. Besides this, Electron spin resonance (ESR) analysis and scavenger experiment results demonstrated that hydroxyl radicals (about 62.3%) and sulfate radicals (about 20.2%) played a major role, while Fe(IV) (about 16.5%) played a minor role in SMT degradation. Moreover, various intermediates for SMT degradation were put forward based on the LC–MS/MS results and their toxicity was predicted to decrease. This work provides a vision for water treatment based on natural mineral materials and presents a new idea for the comprehensive utilization of siderite. © 2023 Society of Chemical Industry (SCI).